Labor market polarization and international macroeconomic dynamics - Federico S. Mandelman (Federal Reserve Bank of Atlanta, 2013)
During the last thirty years, labor markets in advanced economies were characterized by their remarkable polarization. As job opportunities in middle-skill occupations disappeared, employment opportunities concentrated in the highest- and lowest-wage occupations. I develop a two-country stochastic growth model that incorporates trade in tasks, rather than in goods, and reveal that this setup can replicate the observed polarization in the United States. This polarization was not a steady process: the relative employment share of each skill group fluctuated significantly over short-to-medium horizons. I show that the domestic and international aggregate shocks estimated within this framework can rationalize such employment dynamics while providing a good fit to the macroeconomic data. The model is estimated with employment data for different skills groups and trade-weighted macroeconomic indicators.
Keywords: F16; F41; 330; labor market polarization; international business cycles; heterogeneous agents; stochastic growth; two-country models